Few Aspects of Government Primary School Environment at Hathazari Upazilla of Chittagong (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
School health environment is very important for school students. To observe existing school environment we conducted the study. A total of 11 government primary school of hathazari upazilla were studied to observe about few aspects of school environment. The study was conducted during first week of May, 2012. Purposively selected primary schools were physically surveyed by the investigators. The result was as follows: Average students 373, average teachers 8.73 and average staffs were 0.45. Average school area was 23 decimal and average floor space was 2230 sft. 82% schools were provided with tube wells and 100% school had toilet facilities. Only 18% schools provided mid-day meal. Electricity was connected with all schools. Cleanliness was satisfactory in 55% schools and 82% schools were found fenced. There was gap between standard and existing facilities. So, it should be minimized.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i1.19421